2019
DOI: 10.3390/rs11030348
|View full text |Cite
|
Sign up to set email alerts
|

PS-InSAR Analysis of Sentinel-1 Data for Detecting Ground Motion in Temperate Oceanic Climate Zones: A Case Study in the Republic of Ireland

Abstract: Regions of temperate oceanic climate have historically represented a challenge for the application of satellite-based multi-temporal SAR interferometry. The landscapes of such regions are commonly characterized by extensive, seasonally-variable vegetation coverage that can cause low temporal coherence and limit the detection capabilities of SAR imagery as acquired, for instance, by previous ERS-1/2 and ENVISAT missions. In this work, we exploited the enhanced resolution in space and time of the recently deploy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…In this study, a coherence threshold of 0.3 and a recurrence of 50% in all interferograms strategy is applied, the final partially coherent pixels covers 62% of the study area. In addition, using C-band data and PS-InSAR method, only 333 stable PS points are found in 6 km 2 boreal peatlands (~56 PS points /km 2 ), where vegetation is dominated by moss [32].Therefore less stable PS points per km 2 are excepted for C-band in tropical peatlands.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, a coherence threshold of 0.3 and a recurrence of 50% in all interferograms strategy is applied, the final partially coherent pixels covers 62% of the study area. In addition, using C-band data and PS-InSAR method, only 333 stable PS points are found in 6 km 2 boreal peatlands (~56 PS points /km 2 ), where vegetation is dominated by moss [32].Therefore less stable PS points per km 2 are excepted for C-band in tropical peatlands.…”
Section: Discussionmentioning
confidence: 98%
“…Using 161 Sentinel-1 SAR (C-band) images and ISBAS method, Marshall et al, [24] also measured the deformation patterns of tropical peat swamp around Kuala Lumpur International Airport. Fiaschi et al, [32] detected uplift signal of up to 8.9 mm/year and subsidence signal of up to −11.6 mm/year in Irish peatlands by using 124 Sentinel-1A/B images acquired from 4 May 2015 to 1 March 2018 and PS-InSAR method. Although, C-band shows potential in measuring peatlands surface motion, it is likely hard to extract sufficient number of PS points and provide good coverage, particularly over a tropical peatlands area [24].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence that peat vertical motion is related to climate and management raises the possibility that it could be used as an effective, and easily measured, proxy for key metrics of peat condition such as water table depth (WTD) and carbon balance, as well as a tool for evaluating restoration outcomes. A number of recent studies have also suggested that this surface motion can be detected remotely using Interferometric Synthetic Aperture Radar (InSAR) data from satellites such as the European Space Agency's Sentinel-1 mission, and the Japan Aerospace Exploration Agency's Advanced Land Observation Satellite-1 (ALOS-1) (Alshammari et al, 2018;Fiaschi et al, 2019;Marshall et al, 2018;Susanti and Anjasmara, 2019;Zhou et al, 2019;Hoyt et al, 2020). This approach offers clear advantages in terms of the cost, spatial scale and frequency at which information can be obtained, especially for large and remote peatland areas.…”
Section: Introductionmentioning
confidence: 99%
“…As limited by the spatial displacement gradient, the InSAR is normally suitable for detection of slow(13 m/month) to extremely-slow (<16 mm/yr) movement [21]. Commonly used MT-InSAR techniques include PS-InSAR (Persistent Scatterer Interferometry) [22][23][24][25] and SBAS-InSAR [26][27][28][29]. The PS-InSAR method obtains long-term series of ground deformation at the expense of the density of monitoring points in space.…”
Section: Introductionmentioning
confidence: 99%